Determination of predisposing factors for prolonged intensive care in patients with exacerbation of chronic obstructive pulmonary disease - Doganci, Melek; Guler Eraslan Doganay; Mehtap Tunc; Hilal Sazak (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the predisposing factors for lengthy intensive care unit stay of chronic obstructive pulmonary disease patients with acute exacerbation. Method: The retrospective study was conducted after approval from the ethics review committee of Atatürk Sanatorium Training and Research Hospital, Turkey, and comprised data from January 1, 2017, to August 31, 2022, related to acute exacerbation chronic obstructive pulmonary disease patients receiving intensive care unite treatment. Demographics, comorbidities, treatment, length of stay in hospital and in intensive care unit, and nutritional status were evaluated. Data of patients who spent <10 days in intensive care unit formed Group 1, while those having spent 10 days or more formed Group 2 for comparison purposes. Data was analysed using SPSS 22. Results: Of the 460 patients, 366(79.6%) were in Group 1; 224(61.2%) males and 64(38.8%) females with mean age 70.81±11.57 years. There were 94(20.4%) patients in Group 2; 62(66%) males and 32(34%) females with mean age 72.38±10.88 years (p>0.05). Inotropic agent support, need for haemodialysis, timeframe of invasive mechanical ventilation, length of stay in hospital, 1-month mortality, antibiotic use, use of diuretic agent, acute physiology and chronic health evaluation-ii score, nutrition risk in the critically ill score, history of lung malignancy, and pneumonic infiltration on chest radiograph were significantly more frequenttly observed in Group 2 patients (p<0.05). Age, timeframe of invasive mechanical ventilation, and length of stay in hospital were the factors prolonging intensive care unit stay (p<0.05). Conclusion: Higher age, longer invasive mechanical ventilation timeframe and hospital stay with acute exacerbation chronic obstructive pulmonary disease caused a prolonged stay in intensive care unit. Key Words: Acute exacerbation of chronic obstructive pulmonary disease, Mechanical ventilation time, Prolonged intensive care stay, Prolonged hospitalisation.